Sustainability Success Factors in Global Supply Chain : Exploratory multi-case study - Alanen, Jenna (My University, 2024)
Sustainability has become a strategic necessity for companies because of stakeholders increasing expectations and sustainability regulatory requirements. This thesis researches the sustain-ability success factors of Smart Power’s suppliers within the global supply chain. The study aims to identify key sustainability success factors, understand the benefits suppliers gain from sustainability investments, and determine how Smart Power can support its suppliers' sustainability path. Previous research in sustainable supply chain management (SSCM) and frameworks such as the United Nations Sustainable Development Goals (SDGs), Science-Based Targets, and EcoVadis form the theoretical foundation for this study. The research is an exploratory multi-case study with a mixed-methods approach, incorporating quantitative data from EcoVadis scorecards and qualitative data from semi-structured inter-views with Smart Power's top 10 rated suppliers. 17 key success factors across environmental, social, and governance dimensions were identified. Environmental factors include for example, ISO 14001 certification and the use of green energy, while social factors emphasize policies on labor rights and health and safety. Governance factors highlight the importance of anti-corruption policies and regular supplier assessments. Suppliers reported significant benefits derived from their sustainability investments. Benefits include reductions in greenhouse gas emissions, cost savings, enhanced brand reputation, and improved operational efficiency. In addition, findings highlighted the necessity for collaboration, training, and economic support from Smart Power to assist suppliers in overcoming sustainability challenges and improving their sustainability performance. Based on the findings, a sustainability framework for suppliers is develop in order to help them improve their sustainability performance and gain identified benefits. Suggestions for Smart Power include concrete recommendations to support their suppliers effectively. This collaborative approach is crucial for improving the overall sustainability performance of Smart Power’s supply chain and contributing to a more sustainable and resource-efficient future.

Kestävästä kehityksestä on tullut yrityksille strateginen välttämättömyys sidosryhmien kasvavien odotusten ja kestävän kehityksen sääntelyvaatimusten vuoksi. Tässä pro gradussa tutkitaan Smart Powerin toimittajien kestävän kehityksen menestystekijöitä globaalissa toimitusketjussa. Tutkimuksen tavoitteena on tunnistaa keskeiset kestävän kehityksen menestystekijät, ymmärtää, mitä hyötyjä toimittajat saavat kestävän kehityksen investoinneista, ja selvittää, miten Smart Power voi tukea toimittajiensa kestävän kehityksen matkaa. Kestävän toimitusketjun hallinnan (SSCM) aiempi tutkimus ja viitekehykset, kuten YK:n kestävän kehityksen tavoitteet, Science-Based Targets ja EcoVadis muodostavat teoreettisen perustan tälle tutkimukselle. Tutkimus on eksploratiivinen monitapaustutkimus, jossa hyödynnetään monimenetelmällistä lähestymistapaa ja joka sisältää kvantitatiivista tietoa EcoVadis arvioinneista ja kvalitatiivista tietoa teemahaastatteluista Smart Powerin kymmenen parhaiten arvoidun toimittajan kanssa. 17 keskeistä menestystekijää kestävän kehityksen ympäristö-, sosiaali- ja hallintokategorioissa tunnistettiin. Ympäristötekijöitä ovat esimerkiksi ISO 14001 -sertifiointi ja vihreän energian käyttö, kun taas sosiaaliset tekijät korostavat työntekijöiden oikeuksia sekä terveyttä ja turvallisuutta. Hallinnolliset tekijät korostavat korruption vastaisen politiikan ja tavarantoimittajien säännöllisten arviointien merkitystä. Tavarantoimittajat raportoivat saavuttaneensa merkittäviä hyötyjä kestävän kehityksen investoinneistaan. Hyötyihin kuuluvat kasvihuonekaasupäästöjen vähentäminen, kustannussäästöt, brändin maineen kehittäminen ja toiminnan tehostaminen. Lisäksi löydökset korostivat yhteistyön, koulutuksen ja taloudellisen tuen välttämättömyyttä Smart Powerilta, jotka auttavat tavarantoimittajia kestävän kehityksen haasteiden kohtaamisessta ja heidän kestävän kehityksen suorituskyvyn parantamisessa. Tulosten perusteella kehitetään toimittajille kestävän kehityksen viitekehys, jonka avulla he voivat edistää kestävän kehityksen suorituskykyään ja saavuttaa tässä tutkimuksessa tunnistettuja hyötyjä. Suositukset Smart Powerille sisältävät konkreettisia suosituksia tavarantoimittajiensa theokkaaseen tukemiseen. Tämä yhteistyöhön perustuva lähestymistapa on ratkaisevan tärkeä Smart Powerin toimitusketjun kestävän kehityksen suorituskyvyn parantamiseksi ja kestävämmän sekä resurssitehokkaamman tulevaisuuden edistämiseksi.
Keywords: supply chains; success factors; suppliers; sustainable development; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management